2004
DOI: 10.1074/jbc.m310468200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Export across the Inner Membrane of Mitochondria

Abstract: The biogenesis of mitochondria requires the insertion of both nuclear and mitochondrially encoded proteins into the inner membrane. The inner membrane protein Oxa1 plays an important role in this process. Translocation of the terminal intermembrane space domains of subunit 2 of the cytochrome oxidase complex, Cox2, strictly depends on Oxa1. In contrast, other Oxa1 substrates can be inserted independently of Oxa1 function, although at reduced efficiency. A Saccharomyces cerevisiae mutant containing a large dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In mitochondria, similar stop-transfer and post-import pathways for inner membrane insertion exist (33,34), and it has been shown that the presence of prolines in the TMD is a fundamental determinant in the capability of a TMD to be arrested or not in the membrane during translocation. It has been demonstrated that prolines in the TMD cause these helices to be transferred by the translocon to the matrix, disfavoring TMD arrest and transfer to the lipid bilayer (35) and prompting these proteins to be inserted via a conservative sorting process that is similar to the post-import pathway in chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…In mitochondria, similar stop-transfer and post-import pathways for inner membrane insertion exist (33,34), and it has been shown that the presence of prolines in the TMD is a fundamental determinant in the capability of a TMD to be arrested or not in the membrane during translocation. It has been demonstrated that prolines in the TMD cause these helices to be transferred by the translocon to the matrix, disfavoring TMD arrest and transfer to the lipid bilayer (35) and prompting these proteins to be inserted via a conservative sorting process that is similar to the post-import pathway in chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the negative charges in the loop region are not essential for YidC-mediated translocation and that topogenesis in the YidC-only pathway is dictated mostly by the positively charged residues remaining in the cytosol. In contrast, the charges present in the translocated regions of substrates determine the Oxa1p dependence (37).…”
Section: Yidc-mediated Recognition and Insertionmentioning
confidence: 99%
“…Although the mitochondrial import pathways have been elucidated (for review, see Ref. 15) and the mitochondrial export pathway is beginning to yield to analysis (16), the assembly pathway for cytochrome c oxidase is still poorly understood. However, it is now clear that assembly of cytochrome c oxidase requires proteins encoded by a number of different nuclear genes (1,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Among the genes with specific effects on cytochrome c oxidase assembly are three genes (COX10, COX15, and YAH1) required for the synthesis of heme A (25)(26)(27)(28), four genes (SCO1, COX11, COX17, and COX23) required for the recruitment and uptake of copper into mitochondria and its assembly into holocytochrome c oxidase (29 -37), and one gene (OXA1/PET1402) that is part of a translocation channel involved in mitochondrial export (16). In addition to the above genes, there are at least five other genes (PET100, PET117, PET191, COX14, and COX16) (38 -42) that encode proteins that have been proposed to function as "assembly facilitators" (1).…”
mentioning
confidence: 99%